CBT Approach in Handling the Phenomenon of “The Death of Expertise” - Naily Nur Rochmah; Asna (Universitas Muhammadiyah Yogyakarta, 2025)
This study aims to explore the potential of cognitive behavioral therapy (CBT) approach in dealing with the phenomenon of